Factors Influencing Consumers to Purchase Cultured Mushrooms - Divina, Marklynne R.; Rodiris, Lord Jan T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The popularity of mushroom cultivation in the Philippines can be attributed to its minimal input demands, driving its increasing adoption across various sectors. Therefore, the purpose of this study was to ascertain how product quality, social influence, and market accessibility influenced the purchase intention of cultured mushroom consumers. The study also investigated product quality, social influence, market accessibility, and purchase intention. It employed descriptive and correlational study designs, with 165 consumers in the first district of Ilocos Sur serving as respondents. To choose the study participants, it used the convenience sampling technique. A questionnaire that the researcher constructed was used to collect the data. The findings indicated that product quality, social influence, and market accessibility influence the purchase intention of consumers. Finally, to optimize sales, market reach, and market visibility, this study offered recommendations for cultured mushroom growers in the first district of Ilocos Sur.